Systemic Retinoids and Scar Dehiscence - Aksoy, Hasan Mete (Indian J Dermatol, 2019)
Systemic retinoids such as isotretinoin and acitretin are associated with numerous side effects but are therapeutically valuable in dermatological practice. Several studies have reported the wound-healing effects of treatment with concurrent systemic retinoids in addition to surgical treatments. Herein, we describe two patients with scar dehiscence that developed after initiation of systemic retinoid treatment following cutaneous surgery. In Case 1, isotretinoin was thought to decrease collagen production to a greater degree than did degradation during the wound remodeling phase, which resulted in wound dehiscence. In Case 2, acitretin was thought to decrease fibroblast proliferation and collagen production during the proliferation phase of wound healing, which resulted in wound dehiscence. Based on the two presented cases, it is advisable to postpone systemic retinoid treatment for 6 months to 1 year following cutaneous surgery, located especially in cosmetically important sites.